2001
DOI: 10.1046/j.1365-313x.2001.01023.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of five tomato phospholipase D cDNAs: rapid and specific expression of LePLDβ1 on elicitation with xylanase

Abstract: Summary Phospholipase D (PLD, EC 3.1.4.4.) has been implicated in a variety of plant processes, including signalling. In Arabidopsis thaliana a PLD gene family has been described and individual members classified into α‐, β‐ and γ‐classes. Here we describe a second PLD gene family in tomato (Lycopersicon esculentum) that includes three α‐ and two β‐classes. Different expression patterns in plant organs were observed for each PLD. In testing a variety of stress treatments on tomato cell suspensions, PLDβ1 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 64 publications
(102 reference statements)
3
119
0
Order By: Relevance
“…reported increased PLD activity in a rice (Oryza sativa) cell-suspension culture treated with an N-acetylchitooligosaccharide elicitor and implied its involvement in ROS production by making use of exogenous application of PA and n-butanol as a PLD inhibitor. Increased PLD activity has also been found in tomato (Lycopersicon esculentum) cell-suspension cultures treated with the fungal elicitor xylanase (van der Luit et al, 2000) and LePLDβ1 was shown to be transcriptionally up-regulated both in tomato cell-suspensions and in leaves (Laxalt et al, 2001). A study of LePLDβ1-silenced cell-suspensions indicated that this isoform is responsible for the increased elicitor-induced PLD activity and implicated its involvement in ROS production, polyphenol oxidase activity and cell-wall remodeling .…”
Section: Pathogen Interactionsmentioning
confidence: 94%
See 4 more Smart Citations
“…reported increased PLD activity in a rice (Oryza sativa) cell-suspension culture treated with an N-acetylchitooligosaccharide elicitor and implied its involvement in ROS production by making use of exogenous application of PA and n-butanol as a PLD inhibitor. Increased PLD activity has also been found in tomato (Lycopersicon esculentum) cell-suspension cultures treated with the fungal elicitor xylanase (van der Luit et al, 2000) and LePLDβ1 was shown to be transcriptionally up-regulated both in tomato cell-suspensions and in leaves (Laxalt et al, 2001). A study of LePLDβ1-silenced cell-suspensions indicated that this isoform is responsible for the increased elicitor-induced PLD activity and implicated its involvement in ROS production, polyphenol oxidase activity and cell-wall remodeling .…”
Section: Pathogen Interactionsmentioning
confidence: 94%
“…PLD has also been proposed to function as a tether between a protein and membranes (Munnik and Musgrave, 2001). This hypothesis makes use of the twostep transphosphatidylation reaction, and states that the phosphatidyl-PLD intermediate could serve as a transient membrane anchor.…”
Section: Membrane Tetheringmentioning
confidence: 99%
See 3 more Smart Citations